The Words Matter: A Scoping Review Investigating Interpersonal Verbal Communication in Academic Libraries - Boyd, Melanie; Lee, Jennifer; Jones, Rhiannon; Lorenzetti, Diane (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2024)
The academic library milieu is replete with verbal interactions that occur between library staff and patrons, as well as within the library staff cohort. Such communication impacts the quality and results of library support provided to students, faculty and community. It also affects workplace health and productivity. Consequently, among academic library staff, knowledge and awareness of effective language use is a crucial component of professional practice. This scoping review examines and analyzes the published literature for beneficial and detrimental verbatim exemplars of communication in the context of academic libraries. While the review found significant literature addressing categories of interpersonal communication in the academic library, few studies provide verbal exemplars. Given that such exemplars play an important role in understanding language categories, and in augmenting effective language use, this gap in the literature warrants further attention.